Small polygons and toric codes - Brown, Gavin; Kasprzyk, Alexander M. (Elsevier, 2013)
We describe two different approaches to making systematic classifications of plane lattice polygons, and recover the toric codes they generate, over small fields, where these match or exceed the best known minimum distance. This includes a [36,19,12]-code over F_7 whose minimum distance 12 exceeds that of all previously known codes.